Archaeological mapping of Tylliria, Cyprus - Lysandrou, Vasiliki; Agapiou, Athos (My University, 2023)
This dataset was elaborated and updated during the ENGINEER project activities. The dataset includes geospatial information about several known archaeological sites in Tylliria area, Cyprus. This information is the result of archival and other publications indexing.
Η χαρτογράφηση του αρχαιολογικού έργου στην περιοχή Τηλλυρίας